2016
DOI: 10.1186/s12968-017-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal T2 mapping cardiovascular magnetic resonance correlates with adverse clinical outcome in patients with suspected acute myocarditis

Abstract: BackgroundWhile most patients recover from suspected acute myocarditis (sAMC) some develop progressive disease with 5-year mortality up to 20%. Recently, parametric Cardiovascular Magnetic Resonance (CMR) approaches, quantifying native T1 and T2 relaxation time, have demonstrated the ability to increase diagnostic accuracy. However, prognostic implications of T2 values in this cohort are unknown. The purpose of the study was to investigate the prognostic relevance of elevated CMR T2 values in patients with sAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 29 publications
3
66
0
4
Order By: Relevance
“…An additional unique finding of our work is the association between an increase in T2 values and an increase in the risk of adverse cardiac outcomes. Similar associations have been demonstrated in a small cohort of patients with suspected acute myocarditis . It should be noted that some patients in our cohort may have been classified as having BNR instead of no rejection due to abnormal T2 values, since the clinical diagnosis of rejection may have been influenced by CMR findings.…”
Section: Discussionsupporting
confidence: 86%
“…An additional unique finding of our work is the association between an increase in T2 values and an increase in the risk of adverse cardiac outcomes. Similar associations have been demonstrated in a small cohort of patients with suspected acute myocarditis . It should be noted that some patients in our cohort may have been classified as having BNR instead of no rejection due to abnormal T2 values, since the clinical diagnosis of rejection may have been influenced by CMR findings.…”
Section: Discussionsupporting
confidence: 86%
“…Bohnen et al found that native myocardial T1 and T2 measurements provide excellent performance for monitoring the healing of myocarditis with a significant decline based on the stage of acute myocarditis [21]. Spieker et al also found T2 mapping to be a good tool for monitoring myocardial inflammation in patients with suspected acute myocarditis [22]. Alkhalil et al demonstrated that the anatomical area at risk may best be quantified by T1 mapping undertaken in the first week after reperfusion [23].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Unfortunately, the combination of T2W‐STIR and T2 mapping cannot differentiate the intracellular from extracellular oedema. However, the T2 mapping is currently considered as the best approach to detect and quantify myocardial oedema …”
Section: Cmr Indices For Dmd Evaluationmentioning
confidence: 99%
“…However, the T2 mapping is currently considered as the best approach to detect and quantify myocardial oedema. 49…”
Section: T2-weighted Imagingmentioning
confidence: 99%